Xylocopa caerulea and Xylocopa auripennis harbor a homologous gut microbiome related to that of eusocial bees - Gu, Yifan; Han, Wensu; Wang, Yuquan; Liang, Danlei; Gao, Jinglin; Zhong, Yihai; Zhao, Shan; Wang, Shijie (Frontiers in Microbiology, 2023)
Eusocial bees, such as bumblebees and honey bees, harbor host-specific gut microbiota through their social behaviors. Conversely, the gut microbiota of solitary bees is erratic owing to their lack of eusocial activities. Carpenter bees (genus Xylocopa) are long-lived bees that do not exhibit advanced eusociality like honey bees. However, they often compete for nests to reproduce. Xylocopa caerulea and Xylocopa auripennis are important pollinators of wild plants on Hainan Island. Whether they have host-specific bacteria in their guts similar to eusocial bees remains unknown. In this study, we targeted the bacterial 16S rRNA V3-V4 region to investigate the diversity of bacterial symbionts in the fore-mid gut and hindgut of two carpenter bees, X. caerulea and X. auripennis. A maximum of 4429 unique amplicon sequence variants (ASVs) were detected from all samples, belonging to ten different phyla. X. caerulea and X. auripennis shared similar bacterial community profiles, with Lactobacillaceae, Bifidobacteriaceae, and Orbaceae beingdominant in their entire guts. X. caerulea and X. auripennis harbor a highly conserved core set of bacteria, including the genera Candidatus Schmidhempelia and Bombiscardovia. These two bacterial taxa from carpenter bees are closely related to those isolated from bumblebees. The LEfSe analysis showed that Lactobacillaceae, Bifidobacteriaceae, and the genus Bombilactobacillus were significantly enriched in the hindguts of both carpenter bees. Functional prediction suggested that the most enriched pathways were involved in carbohydrate and lipid metabolism. Our results revealed the structure of the gut microbiota in two carpenter bees and confirmed the presence of some core bacterial taxa that were previously only found in the guts of social bees.